If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3) = 2x + -5 Reorder the terms: 3(3 + x) = 2x + -5 (3 * 3 + x * 3) = 2x + -5 (9 + 3x) = 2x + -5 Reorder the terms: 9 + 3x = -5 + 2x Solving 9 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x 9 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 1x = -5 + 0 9 + 1x = -5 Add '-9' to each side of the equation. 9 + -9 + 1x = -5 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = -5 + -9 1x = -5 + -9 Combine like terms: -5 + -9 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| 5h*-5= | | 10.4+12t=-37.6 | | 3(4-x)-(3+x)=8 | | 9x+7=-6+7x+21 | | 16x=-4+15x | | 120=15+22 | | 2+2+2+2=5 | | 4(x-2)-5(3x-9)=0 | | 25=3t+10 | | 4-4a=2a+1-5a | | -24+2=m-6 | | 6h-10=15h-80 | | 14=2+2s | | 3x-11=x+21 | | 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 |